1991
DOI: 10.1037/0735-7044.105.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin selectively increases holding and licking of neonates in preweanling but not postweanling juvenile rats.

Abstract: Preweanling rats exhibit components of maternal behavior (MB) after brief periods of contact with neonates; the latency of onset of MB rises considerably after weaning. Oxytocin (OXT) stimulates MB in adult rats. The effects of intracisternal (1C) administration of OXT (2 ^g) on pup-directed and other behaviors in preweanling and postweanling juvenile rats were tested. Compared with saline and no treatment, OXT significantly increased active holding of pups in preweanling but not postweanling juvenile rats. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Other sites, including the MPOA and AMYG showed enhanced c-fos expression in the adult but not in the juvenile. Similarly, in contrast to the role of these hormones in the adult female rat, neither oxytocin nor prolactin facilitates the expression of maternal behavior in the juvenile female rat (although prolactin seems to be effective in the male juvenile rat) (Kinsley & Bridges, 1988;Peterson, Mason, Barakat, & Pedersen, 1991). Endocrine data also support the idea that the``maternal behavior'' of juvenile and adult animals may not be controlled by identical mechanisms.…”
Section: Discussionmentioning
confidence: 82%
“…Other sites, including the MPOA and AMYG showed enhanced c-fos expression in the adult but not in the juvenile. Similarly, in contrast to the role of these hormones in the adult female rat, neither oxytocin nor prolactin facilitates the expression of maternal behavior in the juvenile female rat (although prolactin seems to be effective in the male juvenile rat) (Kinsley & Bridges, 1988;Peterson, Mason, Barakat, & Pedersen, 1991). Endocrine data also support the idea that the``maternal behavior'' of juvenile and adult animals may not be controlled by identical mechanisms.…”
Section: Discussionmentioning
confidence: 82%
“…For example, preweanling rats (approximately 20 days of age) that received i.c.v. OXT increased holding and licking of pups . Other studies had shown a reduction in OXTR density in the NAc of rats from age 20 days, when naïve male and female rats are prone to display parental behaviour, to adulthood, when naïve male and female rats ignore or avoid newborns .…”
Section: Oxtr Distribution In the Brain Influences The Propensity Of mentioning
confidence: 76%
“…had shown that weanling rats showed parental behaviour with very short latencies. Furthermore, there was one study that also suggested that OXT could facilitate parental behaviour in juvenile or preweanling animals . For example, preweanling rats (approximately 20 days of age) that received i.c.v.…”
Section: Oxtr Distribution In the Brain Influences The Propensity Of mentioning
confidence: 99%
“…The transition from attachment to independence occurring during weaning is unique in the life span, irreversible, and essential for survival, occurring in all mammalian species and every individual animal and is formative of social behavior in many. In contrast, while mating and parenting are affiliative transitions that also have been associated with neurochemical alterations (Carter, 1998;Insel, 1997;Nelson & Panksepp, 1996, 1998Peterson, Mason, Barakat, & Pedersen, 1991), in many mammalian species mating is brief and arguably ''affiliation,'' parenting is often gender (female) specific, these transitions are reversible, recurring, and inessential for the individual's survival; in many species, many or most individuals do not engage in them at all.…”
Section: Discussionmentioning
confidence: 86%